Efficacy and safety of topical clobetasol propionate in comparison with alternative treatments in oral lichen planus: an updated systematic review and meta-analysis - Zheng, Tao; Liu, ChengYong; Wang, YeTong; Zhou, Rong; Wu, Dan; Tan, Jin; Zhu, KeKe (Frontiers in Medicine, 2024)
Background Oral lichen planus (OLP) is a relatively common chronic T cell-mediated disease characterized by pain and inflammation. Clobetasol propionate (CLO) is the first-line drug in the treatment of OLP. The meta-analysis aimed to evaluate the efficacy and safety of CLO for treating patients with OLP. Methods PubMed, Embase and Web of Science were systematically searched from the database inception date up to August 2023. There were no restrictions on language or date of publication. The outcomes of our interest were as follows: improvement of clinical signs and/or symptoms, total lesion size, relapse and adverse events. Results A total of 17 RCTs evaluating the effects of CLO were included in this study. The results revealed no significant difference in the clinical score (WMD = 0.14, 95% CI: −0.39, 0.66; p = 0.609) and pain score (WMD = 0.17, 95% CI: −0.44, 0.79; p = 0.582) between CLO and other treatments. However, clinical resolution (RR = 1.61, 95% CI: 1.17, 2.22; p = 0.003) and symptoms improvement (RR = 1.80, 95% CI: 1.17, 2.77; p = 0.008) were significantly different between CLO and other treatments. Moreover, there was a significant reduction in the total lesion size with CLO treatment (WMD = -0.58, 95% CI: −1.03, −0.13; p = 0.011). In addition, CLO showed no statistical incidence of adverse events (RR = 1.46, 95% CI: 0.86, 2.50; p = 0.161) and relapse (RR = 1.56, 95% CI: 0.66, 3.71; p = 0.314) than other therapies. Conclusion This systematic review and meta-analysis of 17 randomized clinical trials supported the long-term application of CLO as an effective regimen in OLP patients.